Digisexuality in the Digital Age: A Critical Hadith-Based Analysis of Islamic Sexual Ethics and Contemporary Challenges - Damayanti, Diah; Ghifari, Muhammad; Muzakki, Muhammad Asgar (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2025)
The rapid advancement of digital technologies has given rise to the phenomenon of digisexuality—sexual preferences and behaviors mediated by digital devices, either as a supplement to or replacement for human relationships. This new reality poses significant challenges to Islamic sexual ethics, especially concerning the preservation of moral values, human dignity, and family stability. This study offers a critical analysis of digisexuality through the lens of hadith literature, employing a qualitative approach rooted in library research. The primary sources include prophetic traditions related to sexual conduct, as well as contemporary literature on human-technology interactions and Muslim scholarly responses to digital sexual issues. The findings reveal that fundamental prophetic teachings—such as the encouragement of marriage, prohibition of celibacy (tabattul), and self-restraint through fasting—remain highly relevant in guiding sexual behavior amid digital realities. Modern scholars increasingly emphasize the maqasid shariah framework, enabling Islamic ethics to be more adaptive in addressing socio-technological transformations. This study recommends enhanced digital literacy education, multidisciplinary collaboration, and renewed engagement with classical sources, ensuring that Islamic sexual ethics can continue to serve as a moral compass in the digital era. These insights offer a foundation for further policy development and empirical research in Islamic ethics and digital society.